2021
DOI: 10.3390/foods10030502
|View full text |Cite
|
Sign up to set email alerts
|

Using Einkorn and Tritordeum Brewers’ Spent Grain to Increase the Nutritional Potential of Durum Wheat Pasta

Abstract: Brewers’ spent grain (BSG), the major by-product of the brewing industry, can be used as a functional ingredient to increase the nutritional value of cereal-based products. In this work, micronized BSG from the einkorn and tritordeum brewing processes were characterized and used to produce four macaroni pasta formulations enriched with BSG at ratios of 5 g and 10 g/100 g of semolina. Einkorn BSG showed the highest values for all the parameters analyzed—proteins, total dietary fiber (TDF) and total antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 39 publications
5
28
0
Order By: Relevance
“…A similar result was obtained in pasta with okara powder (Pan, Liu and Shiau, 2018;Kamble et al, 2019), partially-deoiled chia flour (Aranibar et al, 2018), grape and pomegranate seeds powder (Koca et al, 2018), and apple and mango peel powder (Lončarić et al, 2014;Jalgaonkar, Jha and Mahawar, 2018). Instead, Zarzycki et al (2020), Sykut-Domanska et al (2020 and Nocente et al, (2021) observed an increase in OCT in pasta fortified with deoiled flaxseed, coconut flours, and brewers' spent grain. The rise in the OCT might be due to the competitive hydration tendency between proteins in the flaxseed and coconut flours, starch, and gluten protein which decreased the starch swelling (Pongpichaiudom and Songsermpong, 2018).…”
Section: Accepted Articlesupporting
confidence: 52%
See 1 more Smart Citation
“…A similar result was obtained in pasta with okara powder (Pan, Liu and Shiau, 2018;Kamble et al, 2019), partially-deoiled chia flour (Aranibar et al, 2018), grape and pomegranate seeds powder (Koca et al, 2018), and apple and mango peel powder (Lončarić et al, 2014;Jalgaonkar, Jha and Mahawar, 2018). Instead, Zarzycki et al (2020), Sykut-Domanska et al (2020 and Nocente et al, (2021) observed an increase in OCT in pasta fortified with deoiled flaxseed, coconut flours, and brewers' spent grain. The rise in the OCT might be due to the competitive hydration tendency between proteins in the flaxseed and coconut flours, starch, and gluten protein which decreased the starch swelling (Pongpichaiudom and Songsermpong, 2018).…”
Section: Accepted Articlesupporting
confidence: 52%
“…Moreover, an increase in the content of resistant starch in fortified pasta and an increment of 39% of the Resistant/Total Starch ratio was observed with the addition of 10g of BSG/100 g (Nocente et al, 2019). Similarly, investigating the nutritional potential of pasta made of einkorn and tridordeum brewers' spent grain, Nocente et al (2021) showed that BSG from both kinds of cereals resulted in pasta with notable increases in protein, TDF, and glucan content.…”
Section: Accepted Articlementioning
confidence: 90%
“…BSG was added at 15% wt/wt in replacement of semolina, based on the pasta technological and sensory acceptability determined in preliminary tests and our previous study on the use of bioprocessed cereal by-products [ 40 ]. Moreover, it was recently reported that the addition of native BSG at percentages lower than 20% minimally affected sensory properties of cooked pasta, identifying the semolina replacement of 10% as the best compromise in terms of technological, nutritional, and sensory pasta features [ 10 , 44 ]. The high content of proteins and fibers of BSG reflected in both the fortified pasta samples compared to the conventional semolina control, independently of the bioprocessing.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of the alternative ingredients used in replacement (albeit partial) of semolina have an enormous impact on the final pasta quality. Fibers interfered with the gluten network development leading to a weaker protein network, with negative consequences on the BSG-containing pasta, such as shorter OCT, lower water absorption during cooking, and higher cooking loss compared to the conventional semolina pasta [ 10 , 44 , 47 , 48 ]. The weakening of the gluten network, as well as the processing conditions affected the micro and macro structure of the pasta (porosity) leading to a faster water diffusion and hence an earlier gelatinization during cooking which explains the shorter OCT [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation